Proposta de desenvolvimento de modelo programa de gerenciamento de riscos ocupacionais – PGR - Ribeiro, Cristiane de Fátima (2022)
Ensuring the health and safety of workers are important elements in the economic, human and environmental aspects of companies. In this context, the PGR - Risk Management Program is a set of processes that makes it possible to establish preventive and corrective actions before the occurrence of accidents at work. Taking into account the importance of activities developed in a Higher Education Institution, the objective of this study is to analyze an operational sector called Infrastructure and Logistics located in the city of Passo Fundo/RS. For the analysis, visits were made to the workplace, interviews with workers using the institution's own forms for data collection where the main risks found were identified, classified as: physical, chemical, biological, ergonomic and accident agents. The quantification of physical and chemical agents was also carried out and the consolidation of information through the risk inventory and action plan. The risk inventory presented in a risk matrix categorized in its severity and probability of occurrence. The action plan considered the risks and dangers analyzed as "Low", "Tolerable", "Moderate" and "Significant". The methods showed that well-prepared documentation is essential to assist in risk management, as in addition to keeping the Institution legally supported, it will contribute to a safer work environment. Finally, the contribution of this study consists in consolidating the information collected and obtaining a PGR proposal for the Institution studied.